2011
DOI: 10.47893/ijcct.2011.1089
|View full text |Cite
|
Sign up to set email alerts
|

Effective Image Clustering with Differential Evolution Technique

Abstract: The paper presents a novel approach of clustering image datasets with differential evolution (DE) technique. The differential evolution is a parallel direct search population based optimization method. From our simulations it is found that DE is able to optimize the quality measures of clusters of image datasets. To claim the superiority of DE based clustering we have compared the outcomes of DE with the classical K-means and popular Particle Swarm Optimization (PSO) algorithms for the same datasets. The compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The parameter settings are configured as: The population size is 10 times of the dimension of data set, and the maximum number of iterations G max is 50. In DE-kmeans algorithm [6][7], the scale factor F is 0.5, and the crossover probability CR is 0.1. In this paper, the scale factor F is a Laplace random number, and the crossover probability CR is self-adaptive.…”
Section: Experiments and Effect Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter settings are configured as: The population size is 10 times of the dimension of data set, and the maximum number of iterations G max is 50. In DE-kmeans algorithm [6][7], the scale factor F is 0.5, and the crossover probability CR is 0.1. In this paper, the scale factor F is a Laplace random number, and the crossover probability CR is self-adaptive.…”
Section: Experiments and Effect Assessmentmentioning
confidence: 99%
“…This guides the search towards an optimal solution for achieving global optimization. The k-means algorithm has been improved by using differential evolution as reported in literatures [6] [7]. It has been shown that differential evolution results in better performance, compared with the k-means algorithms using other evolutionary algorithms like the traditional genetic or particle swarm optimization.…”
Section: Introductionmentioning
confidence: 99%